(untitled) (Revista Educação, Artes e Inclusão, 2020)
The emerging figures presented here - marked by madness, disability, and other lines of risk and desertification - have been drawn since doctoral research “Unworking (Desoeuvrement) – clinical and political constellations of the common”, and continue proliferating in number and potency of differentiation, in contagion with some art, present in attempts by the Ueinzz Theater Company. What is explicit in these drawings are existences that performs your own life, crossed by the theater that this collective intends to produce, since 22 years in the city of São Paulo. The frontier zone between the arts and the clinic, present in this experience, oscillates emphases in a not evident way. By affirming greater visibility to everything that inscribes it in the artistic-cultural field and operate with the clinic in the most subtle and invisible dimensions, this collective supports an ethic of shifting and shuffling the hegemonic codes that establish ways of existing, in an exclusionary operation. The demand for a clinic that prevents the absolute validity of the clinic itself in the life of these figures it is the paradox that this writing must problematize, from immersions in the artistic making of the linving of this collective.